Mobile game development with Unity : build once, deploy anywhere - Manning, Jon; Buttfield-Addison, Paris (O'Reilly Media, 2017)
Do you want to build mobile games, but lack game development experience? No problem. This practical guide shows you how to create beautiful, interactive content for iOS and Android devices with the Unity game engine. Authors Jon Manning and Paris Buttfield-Addison ( iOS Swift Game Development Cookbook ) provide a top-to-bottom overview of Unity's features with specific, project-oriented guidance on how to use them in real game situations.